Pemodelan dan Evaluasi Proses Bisnis Menggunakan Metode Quality Evaluation Framework (QEF) (Studi Kasus : PT. Group Mitra Indonesia) - Dimas Hariyanto Sudarpi; Nanang Yudi Setiawan; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Group Mitra Indonesia is a company engaged in the field of labor security services provider and investigation. The process of serving services to clients is the main business process running on PT. Group Mitra Indonesia. In the service delivery process there are several other processes that start from the offer and agreement of cooperation with the client, the acceptance and selection of labor, and also the placement of workers at the client company. In the process of presenting the service to the client there are some problems that cause the quality of service is bad. So we need to evaluate the current business process using Quality Evaluation Framework (QEF) method. To conduct a business process evaluation today requires the current business process model that is modeled by using Business Process Model and Notation (BPMN). Next phase is mapping the Quality Factor of every business process that has been modeled and determine the target and calculation of the realization at the company using the formula that has been defined in Quality Evaluation Framework (QEF) method. The results of the calculations performed at the evaluation stage will result some inappropriate Quality Factor. fishbone analysis method and 5 whys analysis is used to analyze the nonconformity obtained and is expected to assist the company in obtaining the root of the problem.